Towards eliminating congenital syphilis : an analysis of trends in Syphilis Seroprevalence among females of reproductive age in Northern Cape Province, South Africa, 2003-2012 - Kuonza, Lazarus R. (2026)
Dissertation (MPH (Public Health))--University of Pretoria, 2015.